Equivalence of BCSH and WHO diagnostic criteria for ET - Harrison, C; McMullin, M; Green, A; Mead, A (Nature Publishing Group, 2016)
Correspondences on ‘Clinical impact of bone marrow morphology for the diagnosis of essential thrombocythemia: comparison between the BCSH and the WHO criteria.’ By Gisslinger et al.